MBRS-02. PERSONALIZED IMMUNOTHERAPY WITH TRANSLATABLE RNA NANOPARTICLES TARGETING MEDULLOBLASTOMA. Issue 2 (22nd June 2018) - Sayour, Elias; Mendez-Gomez, Hector; Grippin, Adam; De Leon, Gabriel; Stover, Brian; Flores, Catherine; Pham, Christina; Mitchell, Duane
Abstract: While recurrent medulloblastoma (MB) remains almost uniformly fatal, our group has shown a trend (p=0.07) toward improved survival in patients receiving autologous tumor-RNA pulsed dendritic cells (DCs) coupled with ex vivo expanded total RNA activated T-cells. However, the advancement of autologous cellular therapeutics remains encumbered by significant cost, complexity and time to generation. To circumvent these challenges, we developed a novel treatment platform, which leverages the use of commercially available and clinically translatable nanoparticles (NPs) that can be combined with tumor-derived RNA for near-immediate induction of systemic immunity against MB. We identified a clinically translatable NP formulation for the delivery of RNA to antigen presenting cells for induction of anti-tumor T-cell immunity. When administered intravenously, RNA-NPs increased expression of co-stimulatory molecules on CD11c+ cells throughout reticuloendothelial organs and within the tumor microenvironment; this phenotype was dependent on type I interferon. Targeted inhibition of type I interferon signaling (via INFAR1-mAbs) abrogated anti-tumor immunity mediated by RNA-NPs. We enhanced the immunogenicity of this platform by simply combining mRNAs encoding for immunomodulatory molecules (i.e. HCV-PAMPs, GM-CSF) or by combining RNA-NPs with immune checkpoint inhibitors. Addition of checkpoint inhibitors to RNA-NPs mediated synergistic anti-tumor activity in settings where PD-1 or PD-L1 inhibition alone did not confer therapeutic benefit. In a pre-clinical cellular immunotherapy model targeting an anaplastic murine MB, RNA NPs superseded DCs in mediating anti-tumor activity. Based on these findings, we are exploring the preclinical safety, efficacy and immunologic effects of RNA-NPs targeting malignant brain tumors in canines (UF-IACUC#:201609430) before first in-human evaluation.